A respecification and extension of DeLone and McLean model of IS success in the citizen-centric e-governance - Jafari, Seyed Mohammadbagher; Ali, Noor Azman; Sambasivan, Murali; Said, Mohd Fuaad (IEEE, 2011)
Citizen-centric e-governance is an emerging approach in the case of designing and implementing the e-governance systems with the specific focus on the effectiveness. Based on this perspective, the citizens' needs and values on e-governance have to be put first to make these systems effective. This study is an attempt to explore and propose the needs and values of citizens on the e-governance systems based on the determinants of information system (IS) success in the DeLone and McLean 2003 (D&M 2003) model of IS success. After conducting a comprehensive literature review, this study proposed new determinants of e-governance success and the citizen-centric e-governance success model. This model can be considered as the respecified and extended model of D&M 2003 model of IS success in the specific context of the citizen-centric e-governance systems.